2003
DOI: 10.1007/s00204-003-0498-z
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate increases toxicity of inorganic lead in GT1-7 neurons: partial protection induced by flunarizine

Abstract: Recent studies point to an interaction between the glutamatergic neurotransmitter system and inorganic lead (Pb) neurotoxicity. Pb (1-100 microM) evoked cytotoxicity over the period of 72 h in mouse hypothalamic GT1-7 neurons. Glutamate (0.1 or 1 mM) on its own did not have any effect on cell viability. However, 1 mM glutamate clearly increased Pb-induced cell death at 48 and 72 h. Although flunarizine (0.1-10 microM), an antagonist of L- and T-type voltage-sensitive calcium channels (VSCCs), partially protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 46 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…In experimental models, combined exposure to glutamate and lead as compared to either agent alone increased neuronal cell death via mechanisms involving an elevation in the production of oxygen radicals and a decrease in intracellular GSH defenses against oxidative stress (217). Exposure of mouse embryonic (day 12) spinal cord and dorsal root ganglion cells to low levels of paraquat, exogenous glutamate, and thermal stress, both singly and in combination (218), revealed that paraquat administered alone was associated with cell death in a dose-dependent manner, an effect that was multiplied by heat shock.…”
Section: Environmental and Lifestyle Risk Factors Associated With Salsmentioning
confidence: 99%
“…In experimental models, combined exposure to glutamate and lead as compared to either agent alone increased neuronal cell death via mechanisms involving an elevation in the production of oxygen radicals and a decrease in intracellular GSH defenses against oxidative stress (217). Exposure of mouse embryonic (day 12) spinal cord and dorsal root ganglion cells to low levels of paraquat, exogenous glutamate, and thermal stress, both singly and in combination (218), revealed that paraquat administered alone was associated with cell death in a dose-dependent manner, an effect that was multiplied by heat shock.…”
Section: Environmental and Lifestyle Risk Factors Associated With Salsmentioning
confidence: 99%
“…The toxicity of glutamate generally involves increased Ca 2+ influx, increased generation of ROS, mitochondrial dysfunction, and oxidative stress which, in turn, may cause apoptosis (Chandra et al ., 2000). In a nutshell, glutamate excitotoxicity, lead neurotoxicity, and oxidative stress are considered to be related phenomena causing neuronal damage (Naarala et al ., 1995; Loikkanen et al ., 2003). …”
Section: Introductionmentioning
confidence: 99%
“…However, both glutamate and Zn 2+ are neurotoxic, distinguishing the effects of Zn 2+ and glutamate by using neuronal cells that possess glutamate receptors has proved difficult. GT1-7 cells either lack or possess low levels of ionotropic glutamate receptors and do not exhibit glutamate toxicity (Mahesh et al, 1999 ; Loikkanen et al, 2003 ). Furthermore, we found that GT1-7 cells are much more sensitive to Zn 2+ than other neuronal cells, including PC-12 cells, B-50 cells (a neuroblastoma cell line), or primary cultured neurons of the rat cerebral cortex or hippocampus (Koyama et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%